Study on Fingerprints of Different Organs of Arabidopsis thaliana by Using UPLC/ESI-Q-TOF MS - Zhao, Hongzhi; Wang, Jing; Xie, Chunfeng; Song, Shengyou; Bai, Gang; Luo, Guoan (Asian Journal of Chemistry, 2013)
To investigate the fingerprint of A. thaliana and compare those of the four different organs (rosette leaves, stems, flowers and stem leaves), an ultra performance liquid chromatography coupled with electrospray ionization quadrupole/time of flight mass spectrometry (UPLC/ESI-Q-TOF MS) was employed. Compounds were separated on the C18 column using a gradient elution of acetonitrile and 0.1 % formic acid in water. The principal components analysis was applied for data treatment. Clear discrimination was obtained in the score plot, providing the difference in chemical characteristic of different organs. Twenty compounds including flavone glycosides, oxylipins, aliphatic acids and others were identified based on their high resolution mass spectra and the MS/MS fragmentation pathways. It is concluded that the several compounds (oxophytodienoid acid, sn-2-O-(dinoroxophytodienoyl) monogalactosyl monoglyceride, kaempferitrin, robinin, arabidopside E and arabidopside A) were significant markers in the different organs of A. thaliana.